Sumatera Utara Botanical Conservatory (With Ecology Architecture Design Approach) - Ira Febri Wanty Simatupang; Andalucia (International Journal of Architecture and Urbanism, 2023)
Climate change affects many things, especially plant diversity. Indonesia's number of endangered plant species continues to increase every year. Meanwhile, ex-situ conservation and research facilities are still unavailable in North Sumatra. The conservatory itself has the primary function as a conservation institution that seeks to maintain and breed various types of plants, especially endangered plants, used to protect and preserve nature, education facilities, development of science and technology, and recreation. The research was conducted using the descriptive-analytic method by drawing problems regarding the concept of conservatory design that pays attention to the environment while collecting data and theories related to the conservatory. The conservatory applies an ecological architectural approach that includes harmony between humans and nature; the balance of development between the natural environment and buildings that need to be considered will become a sustainable green building. This project is expected to create a medium for conservation and research beneficial to the community, as educational and interactive tourism facilities between humans and nature that are sustainable and have no negative impact on the environment.